INTEGRASI TEORI BEHAVIORISTIK DALAM PERSPEKTIF IMAM AL-GHAZALI UNTUK MENINGKATKAN DISIPLIN SISWA DI MATA PELAJARAN PAI - Khasan, Nur; Fadhilah, Iman; Imron, Ali (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Student discipline is one of the crucial factors in the success of Islamic Religious Education (IRE). This study aims to integrate behavioristic theory with Imam Al-Ghazali's Islamic educational perspective in an effort to improve student discipline in IRE subjects. The method used is library research with a descriptive-analytical qualitative approach. Data were collected from primary literature in the form of Al-Ghazali's works, such as Ihya Ulumuddin and Ayyuhal Walad, as well as secondary literature, including books, journals, and scientific articles on behaviorist theory and Islamic education. The analysis was conducted through content analysis to find common ground between behaviorist concepts (stimulus-response, reinforcement, punishment) and Al-Ghazali's educational principles (mujahadah, riyadhah, habituation, and exemplary behavior). The results of the study show that there is a fundamental harmony between behaviorist theory and Al-Ghazali's educational concepts, particularly in the aspects of habituation, positive reinforcement, and logical consequences. The integration of these two approaches produces a comprehensive discipline development model, combining external dimensions (behavioral modification) with internal dimensions (spiritual motivation). The implementation of this integrated model shows significant potential in improving student discipline through a holistic approach, not only shaping outward behavior but also inner awareness. This research provides a theoretical contribution to the development of an Islamic values-based character education model that is compatible with modern psychological theory, as well as practical implications for PAI teachers in developing effective and meaningful discipline strategies.